Autologous mastectomy reconstruction: Communication among the breast surgery team to maximize aesthetic and oncologic outcome. Issue 9 (16th May 2020) - Dickinson, Brian P.; Holmes, Dennis; Vu‐Huynh, Nikkie; Vu, Monica B.; Snyder, Lincoln; MacDonald, Heather; Guerra, Lisa; Coleman, Colleen; Fancher, Crystal; Hamoui, Nahid; Khan, Sadia; Kim, Sadie; et al.
Abstract: Mastectomy breast reconstruction with autologous tissue is challenging. Oncologic and aesthetic goals face previous surgical scars, radiation, chemotherapy, or other comorbidities. We describe a simple approach for autologous mastectomy reconstruction so that breast and plastic and reconstructive surgeons can maximize aesthetic outcomes and minimize wound complications. A retrospective chart review was done on patients who underwent mastectomy and autologous reconstruction. The surgical flight plans were reviewed to delineate an approach, and pre‐ and postoperative photographs were examined to create a step‐by‐step process. The most encountered mastectomy and autologous flap reconstruction scenarios were categorized to create a step‐by‐step process. Successful autologous mastectomy reconstruction to optimize aesthetic outcome and minimize complications requires team communication. Creation of a surgical flight plan using information from the physical examination, MRI and adjunctive imaging, and preoperative photographs is imperative. Thoughtful incision choice and exposure approach are paramount.